Fear of falling in older fallers presenting at emergency departments - Hill, Keith; Womer, M.; Russell, M.; Blackberry, I.; McGann, A. (Blackwell Publishing Ltd, 2010)
Aim.: This paper is a report of an investigation of fear of falling in older people presenting to emergency departments after a fall. Background.: Falls are a common and disabling cause of attendance at emergency departments. Fear of falling is an often unrecognized consequence of falls that affects older people's function. Methods.: Sub-analysis was conducted of a randomized trial of a falls prevention programme for people aged 60 years and older presenting to emergency departments after a fall. Data were collected between 2003 and 2006 with 712 participants recruited (mean age 75, 70% female). Baseline and 12-month measurements included fear of falling (Modified Falls Efficacy Scale), falls risk, depression, and balance/mobility measures. Intervention participants received interventions based on assessment findings, while control participants received usual care. Repeated measures analysis of variance and logistic regression were used to determine change over time between groups and factors associated with fear of falling, respectively. Results.: Sixty per cent of participants had fear of falling. Statistically significant improvement occurred in overall fear of falling (repeated measures analysis of variance - F = 37·3; P < 0·001) and 13 of 14 sub-items of the Modified Falls Efficacy Scale at 12 months, but there was no difference between groups. Multivariate logistic regression identified a number of factors associated with statistically significant increased odds of higher fear of falling persisting at12 months, including higher baseline fear of falling and multiple falls in the 12-month follow-up. Conclusion.: Nursing staff in emergency departments have an important role in identifying fear of falling, which may guide the need for referral for further assessment and management after discharge from the emergency department. © 2010 Blackwell Publishing Ltd.